تأثير نفوذ القوى الكبرى على صنع القرار الدولي داخل هيئة الأمم المتحدة - ناصري, سميرة (revue mofakir; No 13 (2016): مجلـــة المفكــر, 2018)
the united nations accomplishes a great progress in the beginning of the composition in achieving many achievements in humanitarian field, most notably the granting of the right of people to self-determination. But the united nations march in the development and progress stalled because of what wrought by international changes after cold war where simplified the US dominance of the UN and has issued many decisions, some of them contradict the Un Charter and bacame circumstances the organization means to wage war and siege on the many nations arround the world. Arabic States received the largest share of the intervention of the great powers in issuing laws against humanitarian as allegations of major powers but the results were exploiting the goodness of people and dismantled and internal ethnic conflicts more serious than most notably Iraq and Syria now. this study will try to discus the reality of the United Nations in the body in the present and some models of the impact of the major powers on the decisions of the organization towards some countriesand their results